2022
DOI: 10.1002/jlb.3hi0422-635r
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral therapy restores the homeostatic state of microglia in SIV-infected rhesus macaques

Abstract: Microglia and macrophages are essential for homeostatic maintenance and innate immune response in the brain. They are the first line of defense against infections such as HIV/SIV in the brain. However, they are susceptible to infection and function as viral reservoirs even under effective viral suppression. While current antiretroviral regimens successfully suppress viremia and improve quality of life and lifespan, neurologic complications persist and are in part attributed to activated microglia. We sought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…For scRNA-seq of microglia, the saline group consisted of samples from animals 74T (referred to as CI47 in ( 57 )), 77T (CK40), 82T (CI04), and 83T (CK03), and the morphine group samples from animals 73T (CK22), 75T (CK48), 78T (CI90), and 80T (CH89). The scRNA-seq data for the three of the members of the saline group, 74T, 82T, and 83T, were reported previously ( 63 ). For the snRNA-seq several animal samples were substituted within the groups due to the availability or suitability of samples for processing and analysis.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…For scRNA-seq of microglia, the saline group consisted of samples from animals 74T (referred to as CI47 in ( 57 )), 77T (CK40), 82T (CI04), and 83T (CK03), and the morphine group samples from animals 73T (CK22), 75T (CK48), 78T (CI90), and 80T (CH89). The scRNA-seq data for the three of the members of the saline group, 74T, 82T, and 83T, were reported previously ( 63 ). For the snRNA-seq several animal samples were substituted within the groups due to the availability or suitability of samples for processing and analysis.…”
Section: Methodsmentioning
confidence: 85%
“…Using scRNA-seq of microglia from SIV-infected animals, we recently found that in untreated animals, microglia exhibited a proinflammatory state, and that viral suppression with cART restored the microglia to a homeostatic-like state ( 63 ). Here we find that in the setting of viral suppression with cART, morphine had numerous other effects on the microglia as well as brain macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…While not as extensively characterized as neurons, they are indeed heterogeneous, and with the advent of scRNA-seq our studies and those of others have identified a number of classes of microglia. (47)(48)(49)(50) To maintain a steady state while gaining some immunogenic properties, microglia express several homeostatic genes. Downregulation and/or mutations of these homeostatic genes can lead to uncontrolled neuroinflammation, neurotoxicity and multiple neurocognitive diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Using scRNA-seq of microglia from SIV-infected animals, we recently found that in untreated animals, microglia exhibited a proinflammatory state, and that viral suppression with cART restored the microglia to a homeostatic-like state (130). Here we find that in the setting of viral suppression with cART, morphine had numerous other effects on the microglia as well as brain macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…For scRNA-seq of microglia, the saline group consisted of samples from animals 74T (referred to as CI47 in (57)), 77T (CK40), 82T (CI04), and 83T (CK03), and the morphine group samples from animals 73T (CK22), 75T (CK48), 78T (CI90), and 80T (CH89). The scRNA-seq data for the three of the members of the saline group, 74T, 82T, and 83T, were reported previously (130). For the snRNA-seq several animal samples were substituted within the groups due to the availability or suitability of samples for processing and analysis.…”
Section: Animalsmentioning
confidence: 99%